Exploring Military Engagement in Education: Opportunities and Challenges from Bangladesh Perspective - Alam, Md Mahbub-ul; Tabassum, Mayeesha; Uddin, Helal (Indonesian Journal of Social Research (IJSR), 2025)
The Bangladesh Army has long contributed to the country’s education sector setting an important example in nation-building. The study aims to assess the contributions, opportunities, and limitations of Army-administered Educational Institutions (AAEIs) and explore their potential role in Madrasah, technical and vocational education, areas where structured governance remains an ongoing national concern. It addresses a key gap in existing literature by examining the research problem.  The study employed a qualitative approach, and the views of administrators, teachers, students, and parents were collected through 70 in-depth interviews (IDI) and four focus group discussions (FGD) using purposive and convenience sampling. Data were analysed through thematic procedures involving coding and category development. Findings indicates that AAEIs have gained widespread trust among parents and students due to their emphasis on discipline, security, efficient management, and moral education while some challenges include higher tuition fees compared to government schools and colleges, difficult to access in cantonment areas, frequent changes of principals, and non-standard student-teacher ratio etc. The study identifies recurring themes related to institutional capabilities, public trust, operational limitations, and future expansion of the Army’s role in diversified education streams. The study recommends that curriculum development, teacher training and technology integration are found necessary to achieve international standards and as a pilot project, the Army may bring about qualitative changes in Madrasah and technical education through efficient administration. At the same time, the research points out the way to transform AAEIs into a sustainable and inclusive education model. The study’s insights carry implications for educational policy and contribute to global discussions on the educational roles of military institutions.